Computational method for the real-time calculation of the full-body muscle load distribution. Issue 7 (18th May 2016) - Shippen, James
Abstract : A method is described for minimising a quadratic function subject to equality and inequality constraints. This approach is applicable to solving the full-body muscle load distribution problem and calculating joint contact loads. It has been found that this approach can provide the solution on modest computing facilities and in significantly less time than using active set and interior point quadratic programming techniques. Hence the approach is suitable for providing real-time feedback to subjects undergoing biomechanical analysis of muscle, skeletal and joint loadings.